FREQUENCY OF HEPATOMA IN PATIENTS WITH CIRRHOSIS ON THE BASIS OF ALPHA FETOPROTEIN AND ULTRASOUND ABDOMEN (The Research of Medical Science Review, 2025)
BACKGROUND: The most common form of primary tumour in the liver is hepatoma, a severe high-grade tumour with fast infiltrative development. It mainly affects those with long-term liver conditions, especially those who have cirrhosis brought on by an infection with hepatitis B or C. OBJECTIVE: To determine the frequency of hepatoma in patients with liver cirrhosis based on alpha-fetoprotein and ultrasound abdomen. Study design: Cross sectional descriptive study Duration of study: 20 th -Nov-2024 to 19 th -Jan-2025 Setting:Department of Gastroenterology and Medicine, Liaquat University Hospital, Hyderabad Sample Size: Total 280 patients with liver cirrhosis Sample technique: Non probability consecutive sampling. PATIENTS AND METHODS: Patients with cirrhosis of the liver, aged 18 to 60, of either gender, were gathered and tested for hepatoma using alpha- fetoprotein and ultrasonography abdomen. Data was gathered using a pre-designed proforma, with frequency (%) and mean ± SD computed for both qualitative and quantitative factors. RESULTS: The mean ± SD values for age (years), duration of liver cirrhosis (months), BMI (kg/m²), and alpha-fetoprotein levels were 52.95 ± 8.54, 18.65 ± 7.92, 30.21 ± 3.63, and 1185.72 ± 98.85, respectively. The study population comprised 161 males (57.5%) and 119 females (42.5%). Additionally, 142 participants (50.7%) were from rural areas, while 138 (49.3%) were from urban areas. The prevalence of obesity, smoking, diabetes mellitus, hypertension, and a family history of malignancy was 49.3%, 48.2%, 54.6%, 55.7%, and 46.1%, respectively. The distribution of etiological factors included hepatitis B virus (26.7%), hepatitis C virus (53.5%), HBV + HCV co-infection (10.7%), and non- viral causes (8.9%). Hepatoma was diagnosed in 178 patients (63.5%) with statistical significance based on alpha-fetoprotein levels (p<0.01) and radiological assessment (p=0.04). CONCLUSION: Hepatoma has been seen in cirrhotic individuals. Thus, patients with chronic liver illness should be regularly followed for liver cancer.